235k views
4 votes
Help -------------------------------

Help --------------------------------example-1
User PhysicsGuy
by
4.6k points

2 Answers

6 votes

Answer:

E + F = 2c² + 5c + 4

Explanation:


E = 6c^2 - 2c - 1 \\\\F = -4c^2 + 7c +5\\\\E + F = (6c^2 - 2 c -1) + ( -4c^2 + 7c +5)


=(6c^2 -4c^2) +(-2c + 7c) + (-1 + 5)
[\ arranging \ terms\ ]


= 2c^2 + 5c + 4

User Juboraj Sarker
by
4.9k points
4 votes

___________________________________

Let's Solve it!

Given that:


\quad\quad\quad\quad\tt{E = 6 {c}^(2) - 2c - 1}


\quad\quad\quad\quad\tt{ F = - 4 {c}^(2) + 7c + 5}

Formula:


\quad\quad\quad\quad\tt{E + F = ?}

Solution:


\quad\quad\quad\tt{(6 {c}^(2) - 2c - 1) + ( - 4 {c}^(2) + 7c + 5)}

Step by step:


\quad\quad\quad\quad\tt{ ⟶(6 {c}^(2) ) + ( - 4 {c}^(2)) = \boxed{ \pink{2 {c}^(2) }}}


\quad\quad\quad\quad\tt{ ⟶ ( - 2c) + ( 7c) = \boxed{ \pink{5c }}}


\quad\quad\quad\quad\tt{ ⟶ ( - 1) + ( 5) = \boxed{ \pink{4 }}}

Now, it will look like this:


\quad\quad\quad\quad\tt{E + F =2 {c}^(2) + 5c + 4 }

So, E + F is equal to:


\quad\quad\quad\quad\tt{\boxed{ \boxed{ \color{magenta}{ 2 {c}^(2) + 5c + 4 }}}}

___________________________________

#CarryOnLearning

✍︎ C.Rose❀

Help --------------------------------example-1
User GuyH
by
4.7k points